Meningkatkan Daya Saing UMKM Desa Punggur Besar Melalui Strategi Pemasaran Digital Berbasis Kecerdasan Buatan (AI) - Anna, Anna; Annisa, Riski; Rahayuningsih, Panny Agustia; Nugraha, Wahyu (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Free Nutritious Meals Program is a social initiative managed by micro, small, and medium enterprises (MSMEs) in Punggur Besar Village to support the nutritional needs of schoolchildren. However, program managers face challenges in increasing visibility, transparency, and community engagement due to limited digital technology capabilities. This activity aims to empower program managers through AI-based digital marketing training that is easily accessible and relevant to their social context. The training was conducted offline at the Punggur Besar Village Office using participatory learning methods and hands-on practice using participants' own devices. Twenty program managers participated in the entire activity. All participants successfully created program-specific social media accounts, produced educational content, and documented activities with the help of AI tools. Eighty percent of participants were able to independently develop content narratives, and seventy-two percent began utilizing basic analytics to understand community responses to their content. The main benefits gained were increased digital communication capacity, strengthened program accountability, and increased confidence in interacting with the public online. This activity demonstrated that the use of AI in digital marketing can be adapted inclusively to strengthen community-based social programs, with the active involvement of managers as key actors in digital transformation at the village level.